Solution of Fractional Kinetic Equations Associated with the p,q-Mathieu-Type Series - D. L. Suthar; S. D. Purohit; Serkan Araci (Discrete Dynamics in Nature and Society)
In this paper, our aim is to finding the solutions of the fractional kinetic equation related with the p,q-Mathieu-type series through the procedure of Sumudu and Laplace transforms. The outcomes of fractional kinetic equations in terms of the Mittag-Leffler function are presented.